Porous zeolite compact
The novel porous zeolite molded body with specific pores addresses the lack of studies on pore diameter and volume, achieving high activity, long life, and low coke deposition for improved catalytic performance.
Patent Information
- Application Number
- JP2023096170
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-24
AI Technical Summary
Existing zeolite compacts used as catalysts lack sufficient studies on optimal pore diameter range and pore volume, affecting their activity, life, and coke deposition, which impacts performance.
A novel porous zeolite molded body with pores in the range of 0.011 to 0.09 μm and a pore volume of 0.04 to 0.8 cc/g, utilizing 10-membered ring zeolites like ZSM-5 and a binder such as silica, to enhance diffusion, adsorption, and catalytic performance.
The novel zeolite molded body exhibits high activity, long life, and low coke deposition, making it effective as a catalyst for aromatization reactions with excellent performance.
Smart Images

Figure 2024177823000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a porous zeolite shaped body containing at least zeolite and a binder, and is expected to be useful as a petrochemical catalyst, an exhaust gas purification catalyst, an adsorbent, and a molecular sieve, and particularly to a novel porous zeolite shaped body in which specific pores have a specific pore volume, and which is expected to be useful as an aromatization reaction catalyst that exhibits excellent performance and stability in the aromatization reaction of aliphatic hydrocarbons. [Background technology]
[0002] Zeolites are widely used industrially as petrochemical catalysts (see, for example, Patent Documents 1 and 2), exhaust gas purification catalysts for internal combustion engines and the like (see, for example, Patent Documents 3 and 4), adsorbents (see, for example, Patent Documents 5 and 6), etc. For industrial use, zeolites are mixed with binders (e.g., silica, alumina, silica alumina, clay minerals, etc.), molded into a predetermined shape, and sintered by high-temperature firing to form a zeolite molded body in which the zeolite and the binder are combined. In this case, the binder is also a factor that affects the performance of the zeolite molded body, and appropriate types, amounts, etc. of the binder have been selected and examined.
[0003] In addition, the pores in zeolite, zeolite molded body, and zeolite composite have a large effect on the diffusion, desorption, release, etc. of the substrate, and mesopores in particular are pores that play an important role in the diffusion of the substrate. Since uniform mesopores have a remarkable effect, zeolites having uniform mesopores have been proposed (see, for example, Patent Document 7). In addition, studies on the size of macropores in molded bodies have been reported (see, for example, Patent Document 8) for use as adsorbents and catalysts that exhibit high performance.
[0004] Furthermore, when zeolite is used as a catalyst, it is expected to have high activity and a long life from the viewpoint of product production efficiency, and also to have a small amount of coke deposited on the molded body due to the reaction from the viewpoint of shortening the time of the combustion regeneration process and suppressing dealumination of the zeolite during combustion.
[0005] Furthermore, catalytic technologies such as petrochemical catalysts and exhaust gas purification catalysts enhance the effective utilization and purification of unused materials, and contribute to the promotion of inclusive and sustainable industries. They are expected to be one of the technologies necessary for a sustainable society, such as the SDGs that have been called for in recent years. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 3580518 [Patent Document 2] Patent No. 3950437 [Patent Document 3] Patent No. 2931332 [Patent Document 4] Patent No. 3311370 [Patent Document 5] Patent No. 6147499 [Patent Document 6] Patent No. 6183580 [Patent Document 7] JP2017-119267A [Patent Document 8] JP 2009-242163 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, at present, there are only limited studies and reports on the range of pore diameters and desirable pore volumes of pores, which have a significant impact not only on activity and lifespan when using zeolite molded bodies as catalysts, but also on the amount of coke, and there are also issues with their performance.
[0008] Therefore, the present invention provides a novel porous zeolite molded body having specific pores with specific pore volumes, which is expected to be used as a petrochemical catalyst, an exhaust gas purification catalyst, an adsorbent, a molecular sieve, and particularly as a catalyst for aromatization reactions. [Means for solving the problem]
[0009] As a result of intensive research conducted by the present inventors to solve the above-mentioned problems, they discovered that a novel porous zeolite molded body in which pores in a specific diameter range have a specific pore volume exhibits excellent performance and stability when used as a catalyst for aromatization reactions, and thus completed the present invention.
[0010] That is, the present invention relates to a porous zeolite molded body comprising at least a zeolite and a binder, characterized in that (1) in the relationship between pore diameter and pore volume measured by mercury intrusion porosimetry, the pore volume of pores having diameters in the range of 0.011 to 0.09 μm is 0.04 to 0.8 cc / g.
[0011] The present invention will be described in detail below.
[0012] The porous zeolite shaped body of the present invention is a porous shaped body containing at least zeolite and a binder, and (i) the pore volume of pores having a diameter in the range of 0.011 to 0.09 μm is in the range of 0.04 to 0.8 cc / g. The relationship between the pore diameter and the pore volume can be measured by mercury intrusion porosimetry, for example, a method of measuring the amount of mercury intrusion using a mercury porosimeter and calculating the amount of mercury intrusion can be mentioned.
[0013] The zeolite constituting the porous zeolite molded body of the present invention is not particularly limited, and may be any zeolite having fine pores. Among them, 10-membered ring fine pore zeolite is preferable because it exhibits excellent performance and stability as an aromatization reaction catalyst capable of stably producing aromatic compounds for a long period of time, and examples thereof include AEL, EUO, FER, HEU, MEU, MEL, MFI, and NES types, and in particular, MFI type zeolite or MEL type zeolite is preferable because it is expected to be a catalyst for aromatization reaction of aliphatic hydrocarbons. For example, MFI type zeolite includes aluminosilicate compounds belonging to the structure code MFI defined by the International Zeolite Society. It may also be a type called ZSM-5.
[0014] The zeolite may be a commercially available product, for example, (product name) HSZ-822HOA (manufactured by Tosoh Corporation, average particle size 5 μm), (product name) HSZ-840HOA (manufactured by Tosoh Corporation, average particle size 10 μm), (product name) HSZ-890HOA (manufactured by Tosoh Corporation, average particle size 10 μm), (product name) HSZ-891HOA (manufactured by Tosoh Corporation, average particle size 4 μm), (product name) HSZ-820NHA (manufactured by Tosoh Corporation, average particle size 5 μm), (product name) HSZ-840NHA (manufactured by Tosoh Corporation, average particle size 10 μm), m), (product name) HSZ-930NHA (manufactured by Tosoh Corporation, average particle size 5 μm), (product name) HSZ-940NHA (manufactured by Tosoh Corporation, average particle size 4 μm), (product name) HSZ-931HOA (manufactured by Tosoh Corporation, average particle size 3 μm), (product name) HSZ-940HOA (manufactured by Tosoh Corporation, average particle size 4 μm), (product name) HSZ-941HOA (manufactured by Tosoh Corporation, average particle size 4 μm), (product name) HSZ-980HOA (manufactured by Tosoh Corporation, average particle size 2.5 μm), (product name) HSZ-720NHA (manufactured by Tosoh Corporation) (Product name) HSZ-720KOA (Product name: Tosoh Corporation, average particle diameter: 20 μm), (Product name) HSZ-642NAA (Product name: Tosoh Corporation, average particle diameter: 12 μm), (Product name) HSZ-620HOA (Product name: Tosoh Corporation, average particle diameter: 18 μm), (Product name) HSZ-640HOA (Product name: Tosoh Corporation, average particle diameter: 12 μm), (Product name) HSZ-660HOA (Product name: Tosoh Corporation, average particle diameter: 12 μm), (Product name) HSZ-690HOA (Product name: Tosoh Corporation, average particle diameter: 12 μm), (Product name) HS Z-500KOA (manufactured by Tosoh Corporation, average particle size 4 μm), (product name) HSZ-341NHA (manufactured by Tosoh Corporation, average particle size 4 μm), (product name) HSZ-371NHA (manufactured by Tosoh Corporation, average particle size 2.5 μm), (product name) HSZ-320NAA (manufactured by Tosoh Corporation, average particle size 7 μm), (product name) HSZ-320HOA (manufactured by Tosoh Corporation, average particle size 7 μm), (product name) HSZ-330HUA (manufactured by Tosoh Corporation, average particle size 7 μm), (product name) HSZ-331HSA (manufactured by Tosoh Corporation, average particle size 2.Examples of such particles include (product name) HSZ-350HUA (manufactured by Tosoh Corporation, average particle diameter 6 μm), (product name) HSZ-360HUA (manufactured by Tosoh Corporation, average particle diameter 6 μm), (product name) HSZ-385HUA (manufactured by Tosoh Corporation, average particle diameter 2.5 μm), and (product name) HSZ-390HUA (manufactured by Tosoh Corporation, average particle diameter 6 μm).
[0015] In addition, as the zeolite, in particular (i) a porous zeolite molded body in which the pore volume of pores in the diameter range of 0.011 to 0.09 μm is in the range of 0.04 to 0.8 cc / g can be efficiently obtained, and in particular, zeolite having an average particle diameter of 1 to 25 μm is preferable, and zeolite having an average particle diameter of 4 to 10 μm is even more preferable. In this case, the average particle diameter can be measured using, for example, a particle size distribution measuring device (product name: Microtrac MT3300EX II, manufactured by Microtrac-Bell Co., Ltd.).
[0016] The binder constituting the porous zeolite shaped body of the present invention may be any binder, further, as long as it belongs to the category called a binding agent or a binder, for example, silica, alumina, silica alumina, clay minerals, etc., can be mentioned, among which silica is preferred because it does not affect the performance when used as a catalyst, particularly as a catalyst for aromatization reaction. There is no limitation on the particle size or agglomeration size of the binder, and among which, a granular binder is preferred because it is easy to handle, and particles with an average particle size of 10 to 100 nm are preferred because they have a high crushing strength when used as a porous zeolite shaped body, and particles with an average particle size of 20 to 100 nm are more preferred because they can efficiently form pores with a diameter of 0.011 to 0.09 μm. In addition, a mixture of a granular binder having an average particle diameter of 20-100 nm and a granular binder having an average particle diameter of 10-20 nm is preferable because it is excellent in the efficiency of forming pores having a diameter of 0.011-0.09 μm and the effect of improving the crushing strength. In this case, the ratio of the granular binder having an average particle diameter of 20-100 nm to the granular binder having an average particle diameter of 10-20 nm is preferably 60-95:40-5 (weight ratio), and more preferably 70-90:30-10 (weight ratio).
[0017] The binder may be a commercially available product, for example, (product name: Snowtex N30G, manufactured by Nissan Chemical Industries, Ltd., average particle diameter: 12 nm), (product name: Snowtex N, manufactured by Nissan Chemical Industries, Ltd., average particle diameter: 12 nm), (product name: Snowtex 30, manufactured by Nissan Chemical Industries, Ltd., average particle diameter: 12 nm), (product name: Snowtex O, manufactured by Nissan Chemical Industries, Ltd., average particle diameter: 12 nm), (product name: Snowtex C, manufactured by Nissan Chemical Industries, Ltd., average particle diameter: 12 nm), (product name: Snowtex AK, manufactured by Nissan Chemical Industries, Ltd., average particle diameter: 12 nm), (product name: Snowtex N-40, manufactured by Nissan Chemical Industries, Ltd., average particle diameter: 22 nm), (product name: Snowtex 50-T, manufactured by Nissan Chemical Industries, Ltd., average particle diameter: 22 nm), (product name: Snowtex O-40, manufactured by Nissan Chemical Industries, Ltd., average particle diameter: 12 nm), diameter 22 nm), ((trade name) Snowtex CM, manufactured by Nissan Chemical Industries, Ltd., average particle diameter 22 nm), ((trade name) Snowtex 30L, manufactured by Nissan Chemical Industries, Ltd., average particle diameter 45 nm), ((trade name) Snowtex OL, manufactured by Nissan Chemical Industries, Ltd., average particle diameter 45 nm), ((trade name) Snowtex AK-L, manufactured by Nissan Chemical Industries, Ltd., average particle diameter 45 nm), ((trade name) Snowtex YL, manufactured by Nissan Chemical Industries, Ltd., average particle diameter 60 nm), ((trade name) Snowtex OYL, manufactured by Nissan Chemical Industries, Ltd., average particle diameter 60 nm), ((trade name) Snowtex AK-YL, manufactured by Nissan Chemical Industries, Ltd., average particle diameter 60 nm), ((trade name) Snowtex ZL, manufactured by Nissan Chemical Industries, Ltd., average particle diameter 80 nm), ((trade name) MP-1040, manufactured by Nissan Chemical Industries, Ltd., average particle diameter 100 nm).
[0018] The porous zeolite shaped body of the present invention has (i) a pore volume of pores having a diameter of 0.011 to 0.09 μm of 0.04 to 0.8 cc / g, more preferably 0.06 to 0.5 cc / g, and even more preferably 0.08 to 0.2 cc / g. If the pore volume of pores having a diameter of 0.011 to 0.09 μm is less than 0.04 cc / g, the pores will not diffuse sufficiently even if the zeolite shaped body is porous, resulting in poor adsorption performance and poor catalytic performance when used as a catalyst. If the pore volume of pores having a diameter of 0.011 to 0.09 μm is more than 0.8 cc / g, the macroscopic void ratio of the shaped body will be large, resulting in low crushing strength and easy collapse of the shaped body.
[0019] Furthermore, since the porous zeolite molded body of the present invention has excellent diffusion, particularly within its pores, and excellent adsorption performance, and further excellent catalytic performance when used as a catalyst, (ii) the pore volume of pores in the diameter range of 0.09 to 200 μm is preferably 0.1 to 0.8 cc / g, and more preferably 0.2 to 0.6 cc / g.
[0020] The novel porous zeolite shaped body of the present invention contains at least zeolite and a binder, and the mixing ratio is arbitrary. In particular, since the shaped body is expected to have excellent performance as a catalyst for aromatization reaction, the binder is preferably 5 to 100 parts by weight, more preferably 10 to 60 parts by weight, per 100 parts by weight of zeolite.
[0021] The novel porous zeolite molded body of the present invention may be produced by any method, for example, by mixing zeolite and a binder, and optionally further additives such as cellulose and water in a predetermined ratio, forming the mixture into a predetermined shape, and sintering it to produce a molded body. The firing temperature in this case is preferably 400 to 800°C, since it is possible to easily produce a molded body having pores that satisfy the above characteristics (i) and further (ii).
[0022] The porous zeolite molded body of the present invention may have any shape, for example, a cylindrical shape, a cylindrical shape, a polygonal prism shape such as a triangular prism shape, a square prism shape, a pentagonal prism shape, a hexagonal prism shape, or a polygonal cylinder shape such as a hollow polygonal prism shape, and among them, a cylindrical shape, a cylindrical shape, or a polygonal prism shape is preferable because it is excellent in continuous productivity and produces a molded body with high pressure collapse strength. In addition, the size such as the diameter, width, length, etc., and the density such as the bulk density and true density can be arbitrarily selected in consideration of the packing efficiency, etc. Furthermore, there is no limitation on the form when using, and the molded body can be crushed and classified into an appropriate size and shape before use as necessary.
[0023] When the porous zeolite shaped body of the present invention is used as a catalyst such as a petrochemical catalyst or an exhaust gas purification catalyst, it may contain metal species by treatment such as impregnation, ion exchange, physical mixing, and vapor deposition. Examples of the metal species in this case include silver, platinum, palladium, tungsten, gallium, zinc, copper, iron, calcium, and compounds, ions, and coordinates thereof. There is no limitation on the type or combination of metal species, and they may be selected according to the purpose. Among them, zinc species are preferable as an aromatization reaction catalyst capable of highly selectively and stably producing aromatic compounds from hydrocarbons.
[0024] By using the porous zeolite shaped article of the present invention as a catalyst for aromatization reaction, it becomes a catalyst excellent in efficiency such as reaction selectivity and productivity, and for example, by contacting it with an aliphatic hydrocarbon and / or alicyclic hydrocarbon having 10 or less carbon atoms, particularly 3 to 8 carbon atoms, it becomes possible to efficiently produce aromatic compounds. In this case, the aliphatic hydrocarbon and / or alicyclic hydrocarbon may be any that falls within the category, such as propane, propylene, cyclopropane, cyclopropene, butane, butene, butadiene, cyclobutane, cyclobutene, pentane, pentene, cyclopentane, cyclopentene, hexane, hexene, hexadiene, cyclohexane, cyclohexene, heptane, heptene, cycloheptane, cycloheptene, octane, octene, cyclooctane, cyclooctene, etc., and mixtures thereof. These hydrocarbons may be derived from petroleum such as naphtha, or may be derived from plants such as bioethanol and bionaphtha, or may be derived from chemically recycled resins such as polyolefins and polystyrene.
[0025] In the reaction according to the embodiment, the reaction temperature is not particularly limited as long as it is possible to produce aromatic compounds, and a range of 400 to 650°C is preferable since it is particularly excellent in production efficiency. There is also no limitation on the reaction pressure, and operation is possible within a pressure range of, for example, about 0.1 MPaA to 2 MPaA. In addition, the supply of the reaction raw material to the aromatization catalyst in this case is not particularly limited as the ratio of the volume of the raw material gas to the volume of the catalyst, and can be, for example, 50 h. -1 ~2000h -1 When aliphatic hydrocarbons and / or alicyclic hydrocarbons are supplied as a raw material gas, they may be used as a single gas, a mixed gas, or a gas diluted with a single or mixed gas selected from an inert gas such as nitrogen, hydrogen, carbon monoxide, and carbon dioxide.
[0026] The reaction type is not limited, and for example, not only fixed bed, transport bed, fluidized bed, moving bed, and multi-tubular reactor, but also continuous flow type, intermittent flow type, and swing type reactors can be used.
[0027] The aromatic compound produced is not particularly limited as long as it belongs to the category called aromatic compounds, and examples thereof include benzene, toluene, xylene, trimethylbenzene, ethylbenzene, propylbenzene, butylbenzene, naphthalene, methylnaphthalene, etc., and in particular, benzene, toluene, and xylene are preferred. Effect of the Invention
[0028] The porous zeolite molded body of the present invention, which contains at least zeolite and a binder, is a novel molded body in which pores in a specific pore diameter range have a specific pore volume, and is expected to be industrially useful as a catalyst and adsorbent. In particular, when used as a catalyst for aromatization reactions, it not only has high activity and a long life, but also exhibits high performance as a catalyst that produces a low amount of coke. [Brief description of the drawings]
[0029] [Figure 1] FIG. 3 is a graph showing the relationship between pore size and pore volume of the porous zeolite molded body obtained in Example 1. [Diagram 2] FIG. 3 is a graph showing the relationship between pore size and pore volume of the porous zeolite molded body obtained in Example 2. [Diagram 3] FIG. 2 is a graph showing the relationship between pore size and pore volume of the porous zeolite molded body obtained in Comparative Example 1. [Figure 4] FIG. 2 is a graph showing the relationship between pore size and pore volume of the porous zeolite molded body obtained in Comparative Example 2. EXAMPLES
[0030] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0031] The measurements and evaluations in the examples and comparative examples are shown below.
[0032] ~Pore distribution, pore size-pore volume measurement~ Using a mercury porosimeter (product name: POREMASTER GT, manufactured by Quantachrome Instruments), 0.6 g of the porous zeolite molded body was placed in a measurement cell (0.5 cc glass cell) and the amount of mercury intrusion under each measurement pressure was measured. The amount of mercury intrusion was obtained by subtracting the amount intrusion during measurement of the blank cell as a base. The volume of pores with diameters in the range of 0.006 to 200 μm was obtained by integrating the amount of mercury intrusion. The pore volume was analyzed using analysis software (product name: Poremaster for WindowsR, manufactured by Quantachrome Instruments). The surface tension of mercury was 480 erg / cm 2 The forward movement angle of the mercury was set to 140°.
[0033] ~Measurement of crushing strength~ A push-pull gauge (Model RX-100, manufactured by Aiko Engineering Co., Ltd.) was installed on an electric stand (Model 2257, manufactured by Aiko Engineering Co., Ltd.) to measure the crushing strength of the porous zeolite molded bodies. As a pretreatment, the samples were heated to 300°C under vacuum and dried for 3 hours. The measurement was performed 25 times for each sample, and the average value was taken as the crushing strength.
[0034] ~Aromatic compound manufacturing apparatus and its manufacturing method~ The obtained porous zeolite molded body was prepared as a catalyst for aromatization reaction by the following method, and aromatic compounds were produced and the performance was evaluated.
[0035] (Method for preparing catalyst for aromatization reaction) Using a muffle furnace capable of passing gas, the porous zeolite molded body was heated to 600°C, and steam treatment was performed by passing a mixed gas of 2NL / min of air and 2NL / min of water for 6 hours, and the temperature was lowered to room temperature. Next, 200g of the porous zeolite molded body was stirred in 1000ml of 1460mmol / l zinc acetate solution for 30 minutes, followed by solid-liquid separation, which was repeated three times. Then, 200g of the porous zeolite molded body was stirred in 1000ml of pure water for 30 minutes, followed by solid-liquid separation, which was repeated five times. A porous zeolite molded body containing zinc seeds was obtained by solid-liquid separation, and was prepared as a catalyst for aromatization reaction by drying at 180°C overnight.
[0036] (Production of aromatic compounds) A fixed-bed gas-phase flow reactor having a stainless steel reaction tube (inner diameter 16 mm, length 1400 mm) was used. The middle part of the stainless steel reaction tube was filled with an aromatization catalyst, and after 1 hour of heat pretreatment at 530°C under a flow of dry air at 100 Nml / min, the raw material mixed gas was fed for 48 hours. A ceramic tubular furnace was used for heating, and the temperature of the aromatization catalyst layer was controlled. The reaction outlet gas and reaction liquid were collected, and the gas and liquid components were analyzed individually using a gas chromatograph. The gas components were analyzed using a gas chromatograph (Shimadzu Corporation, (trade name) GC-1700) equipped with a TCD detector and a packing (Waters, (trade name) PorapakQ or GL Science, (trade name) MS-5A). The liquid components were analyzed using a gas chromatograph (Shimadzu Corporation, product name: GC-2015) equipped with an FID detector and having a capillary column (GL Sciences, product name: TC-1) as a separation column.
[0037] The reaction conditions were set as follows:
[0038] (Aromatic compound manufacturing conditions) Raw material mixed gas: a mixed gas of 1-butene 123.3 Nml / min, 2-butene 93.0 Nml / min, isobutene 231.6 Nml / min, normal butane 44.1 Nml / min, isobutane 9.1 Nml / min, and propane 71.1 Nml / min. Catalyst for aromatization reaction: 70g. Reaction temperature: 530°C. Reaction pressure: 150kPaG (C4 conversion rate, aromatic yield) Calculation was made using the following formula. (1) C4 conversion rate (%) = (1 - (weight of unreacted butanes + butenes / weight of butanes + butenes in the raw material mixed gas)) x 100 (2) Aromatic yield (wt%) = (weight of benzene + toluene + xylene + ethylbenzene / weight of raw material hydrocarbon) x 100 ~Amount of coke deposited~ Using a differential thermobalance (product name STA 2500 Regulus, manufactured by NETZSCH), the aromatization catalyst on which the coke had accumulated was heated to 800°C at a heating rate of 10°C / min under a mixed gas flow of 80 Nml / min of air and 20 Nml / min of nitrogen, and the coke was completely combusted. The weight of the coke accumulated per weight of the molded body was calculated by subtracting the weight change due to the desorption of water and light hydrocarbons adsorbed in the molded body from the total weight change.
[0039] Example 1 A kneaded mixture was prepared by mixing 100 parts by weight of commercially available MFI type zeolite (product name: HSZ-822HOA, manufactured by Tosoh Corporation, ZSM-5 powder, average particle size: 5 μm, SiO2 / Al2O3 ratio: 24) with 25 parts by weight of commercially available silica (product name: Snowtex 50-T, manufactured by Nissan Chemical Industries, Ltd., average particle size: 22 nm), 5 parts by weight of cellulose, and 36 parts by weight of pure water.
[0040] The kneaded product was then formed into a cylindrical molded body having a diameter of 3.0 mm and a length of 4.0 to 7.0 mm (average length 5.6 mm), and dried overnight at 100°C. The dried molded body was fired at 600°C for 2 hours in air circulation to obtain a porous zeolite molded body. The physical properties of the obtained porous zeolite molded body are shown in Table 1. The relationship between pore diameter and pore volume is shown in Figure 1.
[0041] The obtained porous zeolite molded body was heated at 600°C using a muffle furnace, and steam treatment was performed by passing a mixed gas of 2NL / min of air and 2NL / min of water for 6 hours, and the temperature was lowered to room temperature. Next, 200g of the porous zeolite molded body was stirred in 1000ml of 1460mmol / l zinc acetate solution for 30 minutes, followed by solid-liquid separation. This operation was repeated three times. Then, 200g of the porous zeolite molded body was stirred in 1000ml of pure water for 30 minutes, followed by solid-liquid separation. This operation was repeated five times. A porous zeolite molded body containing zinc was obtained by solid-liquid separation, and was prepared as a catalyst for aromatization reaction by drying at 180°C overnight.
[0042] Using the obtained aromatization catalyst, aromatic compounds were produced under the above-mentioned aromatic compound production conditions, and the aromatization evaluation results are shown in Table 2. The catalyst had high activity and high aromatic yield, and had a long life with a sufficiently high final C4 conversion rate. In addition, the amount of coke was low, and it showed excellent performance as an aromatization catalyst.
[0043] [Table 1]
[0044] [Table 2]
[0045] Example 2 A porous zeolite molded body was obtained in the same manner as in Example 1, except that commercially available silica (product name Snowtex 30L, manufactured by Nissan Chemical Industries, Ltd., average particle size 45 nm) was used and 29 parts by weight of pure water was used, and the body was prepared and evaluated as an aromatization reaction catalyst. The results are shown in Tables 1 and 2. The relationship between pore size and pore volume is shown in Figure 2. The catalyst had high activity and high aromatic yield, and had a long life with a sufficiently high final C4 conversion rate. In addition, the catalyst showed excellent performance as an aromatization catalyst with a low coke amount.
[0046] Example 3 A porous zeolite molded body was obtained in the same manner as in Example 1, except that commercially available silica (product name Snowtex YL, manufactured by Nissan Chemical Industries, Ltd., average particle size 60 nm) was used and 26 parts by weight of pure water was used, and the body was prepared and evaluated as an aromatization reaction catalyst. The results are shown in Tables 1 and 2. The catalyst had high activity and high aromatic yield, and had a long life with a sufficiently high final C4 conversion rate. In addition, the amount of coke was low and the catalyst showed excellent performance as an aromatization catalyst.
[0047] Example 4 A porous zeolite molded body was obtained in the same manner as in Example 1, except that commercially available silica (product name Snowtex ZL, manufactured by Nissan Chemical Industries, Ltd., average particle size 80 nm) was used and 26 parts by weight of pure water was used, and the body was prepared and evaluated as an aromatization reaction catalyst. The results are shown in Tables 1 and 2. The catalyst had high activity and high aromatic yield, and had a long life with a sufficiently high final C4 conversion rate. In addition, the amount of coke was low and the catalyst showed excellent performance as an aromatization catalyst.
[0048] Example 5 A porous zeolite molded body was obtained in the same manner as in Example 1, except that commercially available silica (product name Snowtex ZL, manufactured by Nissan Chemical Industries, Ltd., average particle size 80 nm) was used and 53 parts by weight of pure water was used, and the product was prepared and evaluated as an aromatization reaction catalyst. The results are shown in Tables 1 and 2. The catalyst had high activity and high aromatic yield, and had a long life with a sufficiently high final C4 conversion rate. In addition, the amount of coke was low and the catalyst showed excellent performance as an aromatization catalyst.
[0049] Example 6 A porous zeolite molded body was obtained in the same manner as in Example 1, except that 20 parts by weight of commercially available silica (product name Snowtex ZL, manufactured by Nissan Chemical Industries, Ltd., average particle size 80 nm), 5 parts by weight of commercially available silica (product name Snowtex 30, manufactured by Nissan Chemical Industries, Ltd., average particle size 12 nm), and 22 parts by weight of pure water were used, and the product was prepared and evaluated as an aromatization reaction catalyst. The results are shown in Tables 1 and 2. The catalyst had high activity and high aromatic yield, and had a long life with a sufficiently high final C4 conversion rate. In addition, the catalyst showed excellent performance as an aromatization catalyst with a low coke amount.
[0050] Example 7 A porous zeolite molded body was obtained in the same manner as in Example 1, except that 20 parts by weight of commercially available silica (product name Snowtex 30L, manufactured by Nissan Chemical Industries, Ltd., average particle size 45 nm), 5 parts by weight of commercially available silica (product name Snowtex 30, manufactured by Nissan Chemical Industries, Ltd., average particle size 12 nm), and 29 parts by weight of pure water were used, and the product was prepared and evaluated as an aromatization reaction catalyst. The results are shown in Tables 1 and 2. The catalyst had high activity and high aromatic yield, and had a long life with a sufficiently high final C4 conversion rate. In addition, the catalyst showed excellent performance as an aromatization catalyst with a low coke amount.
[0051] Comparative Example 1 A porous zeolite molded body was obtained in the same manner as in Example 1, except that 25 parts by weight of commercially available silica (product name Snowtex 30, manufactured by Nissan Chemical Industries, Ltd., average particle size 12 nm) and 29 parts by weight of pure water were used, and the body was prepared and evaluated as an aromatization reaction catalyst. The results are shown in Tables 1 and 2, and the relationship between pore size and pore volume in Figure 3. The catalyst had low activity and low aromatic yield, and the final C4 conversion was low, making it unsuitable for a long-term reaction of 48 hours. In addition, the amount of coke was high, and the performance as an aromatization reaction catalyst was poor.
[0052] Comparative Example 2 A porous zeolite molded body was obtained in the same manner as in Example 1, except that 25 parts by weight of commercially available silica (product name Snowtex N30G, manufactured by Nissan Chemical Industries, Ltd., average particle size 12 nm) and 30 parts by weight of pure water were used, and the body was prepared and evaluated as an aromatization reaction catalyst. The results are shown in Tables 1 and 2. The relationship between pore size and pore volume is shown in Figure 4. The catalyst had low activity and low aromatic yield, and the final C4 conversion was low, making it unsuitable for a long-term reaction of 48 hours. In addition, the amount of coke was high, and the performance as an aromatization reaction catalyst was poor. [Industrial Applicability]
[0053] A porous zeolite molded body having a pore volume within a specific range for pores having a diameter within a specific range is not only highly active and has a long life, particularly in the aromatization reaction of aliphatic hydrocarbons, but is also expected to be useful as an aromatization reaction catalyst that produces a low amount of coke, and is therefore of great industrial value.
Claims
1. A porous zeolite shaped body comprising at least a zeolite and a binder, characterized in that (1) in the relationship between pore diameter and pore volume as determined by mercury intrusion porosimetry, the pore volume of pores having diameters in the range of 0.011 to 0.09 μm is 0.04 to 0.8 cc / g.
2. The porous zeolite shaped body according to claim 1, further characterized in that (ii) in the relationship between pore diameter and pore volume as determined by mercury intrusion porosimetry, the pore volume of pores having diameters in the range of 0.09 μm to 200 μm is 0.1 to 0.8 cc / g.
3. 3. The porous zeolite molded body according to claim 1, wherein the blending ratio of the zeolite to the binder is 5 to 100 parts by weight per 100 parts by weight of the zeolite.
4. 3. The porous zeolite formed body according to claim 1, wherein the zeolite is a granular zeolite having an average particle size of 1 to 25 μm, and the binder is a granular binder having an average particle size of 10 to 100 nm.
5. 3. The porous zeolite shaped body according to claim 1, having at least one shape selected from the group consisting of a cylinder, a cylindrical column, a polygonal prism, and a polygonal cylinder.
6. 3. The porous zeolite shaped article according to claim 1, wherein the zeolite is a 10-membered ring pore zeolite, and the binder is silica.
7. 2. The porous zeolite shaped body according to claim 1, further comprising a metal species.
8. 8. The porous zeolite shaped body according to claim 7, wherein the metal species is a zinc species.
9. A catalyst for aromatization reaction, comprising the porous zeolite shaped article according to claim 7 or 8.
Citation Information
Patent Citations
Manufacture of antibiotic l17046
JP1986047499A
display
JP1986083580A
Method of manufacturing activated alumina shaped article
JP2009242163A
Catalyst for manufacturing aromatic compound and method for manufacturing aromatic compound
JP2017119267A
Method for reducing nitrogen oxides in waste gas using zeolite-containing catalyst
JP2931332B2
